MOVARAUNNAKHR'S HISTORY AS A COMMERCIAL AND ECONOMIC CENTER OF THE TIMURID KINGDOM - Odilova Ziyoda; Turdaliyeva Odina (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The article examines the economic policy of Amir Temur's powerful and huge state and its role in the life of the peoples of Central Asia. We know that the era of Amir Temur and the Timurids in the 14th-15th centuries is a "golden age" as a period of renaissance in the history of Central Asia. Currently, the formation of a national economic idea for the economic stability of the country has always been considered an urgent issue. In this article, Amir Temur and The conditions created for the development of external and internal trade relations within the framework of the economic reforms during the Timurid period are analyzed, and at the same time, the importance of fundamental changes in the socio-economic life of our country is shown. It is a fundamental basis for the further development of our thinking, and its practical use will undoubtedly make a significant contribution to the economic growth of our country.